2015
DOI: 10.1179/1754762814y.0000000107
|View full text |Cite
|
Sign up to set email alerts
|

Pain-only complaint about cochlear implant device: A five-patient pediatric experience

Abstract: Pain may be the sole clinical manifestation of cochlear implant device failure. We offer a flowchart for the care of CI patients with pain, encourage a worldwide registry of such cases, and offer ideas to try to understand better the problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 6 publications
4
6
0
Order By: Relevance
“…Prior studies included 4, 5, or 10 device explantations. [4][5][6] Our results confirm a previous observation that this complication occurs most commonly in females several years after device implantation. 6 Importantly, we observed that idiopathic pain with bacterial device-site infection most often occurred after sequential cochlear implantation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Prior studies included 4, 5, or 10 device explantations. [4][5][6] Our results confirm a previous observation that this complication occurs most commonly in females several years after device implantation. 6 Importantly, we observed that idiopathic pain with bacterial device-site infection most often occurred after sequential cochlear implantation.…”
Section: Discussionsupporting
confidence: 90%
“…This idiopathic persistent CI pain may severely limit use of the device and may necessitate revision surgery despite not elucidating the cause for pain. [4][5][6] Prior studies of persistent CI pain have reported a prevalence rate ranging from 0.86% to 2.8% of implanted patients. [4][5][6] This pain often presents in a delayed timeframe postoperatively, with a mean of 5.8 years in one study.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent reimplantation was uneventful and no reason for initial pain onset could be identified. 6 There have been studies published mentioning neo-ossification that was found in revision surgery, but this was related to the ossification of the cochlea and the mastoid cavity. 7 One study found that intracochlear osseous tissue was more present in cases where the electrode was folded, though that was not the case in our patient.…”
Section: Discussionmentioning
confidence: 99%